Preparation method and application of aerogel for separating panax notoginseng saponins

A composite aerogel made from modified montmorillonite and nanocellulose effectively purifies Panax notoginseng total saponins, offering a green alternative to traditional styrene resin methods by achieving high adsorption efficiency and reducing environmental impact.

CN119236884APending Publication Date: 2025-01-03GUANGXI UNIV FOR NATITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410985308.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Current methods for separating and purifying Panax notoginseng total saponins rely on non-renewable styrene resin, leading to environmental pollution, and there is a lack of research on green and environmentally friendly biomass adsorbents for this purpose.

Method used

A composite aerogel is prepared by acid-organically modifying montmorillonite and combining it with nanocellulose through freeze-drying to create a modified montmorillonite-nanocellulose composite aerogel for the separation and purification of Panax notoginseng total saponins.

Benefits of technology

The composite aerogel provides a green and effective adsorption method for Panax notoginseng total saponins, with optimal conditions achieving an adsorption amount of 49.6 mg/g and an adsorption rate of 95.1%, addressing the environmental concerns of traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236884A_ABST
    Figure CN119236884A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of aerogel for separating panax notoginseng saponins, which comprises the following steps: carrying out acidic modification on montmorillonite K10 (MK), intercalating montmorillonite through an organic surfactant cetyltrimethylammonium bromide (CTAB) to obtain modified montmorillonite (OMA), dissolving polyvinyl alcohol (PVA) in a nanocellulose suspension (1.3 wt%, CNF), and carrying out ultrasonic dispersion to obtain the aerogel. Adding modified montmorillonite, stirring and dispersing uniformly, and freeze-drying to obtain the green and environment-friendly biomass adsorbent. At present, styrene resin is mainly used for adsorbing panax notoginseng saponins (PNS), petrochemical engineering is used as a raw material, and research on green and environment-friendly biomass adsorbents is less; montmorillonite has the advantages of being large in specific surface area, good in adsorption capacity and the like, nanocellulose has the characteristics of being high in specific surface area, environmentally friendly, renewable and the like, cellulose aerogel serves as a porous material and is widely applied to the adsorption field, the biomass adsorbent is prepared by combining the characteristics of the two materials and used for separating and purifying panax notoginseng saponins, the preparation method is simple, and the cost is low. The environment is protected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of separation and purification of notoginseng total saponins, and particularly relates to a preparation method and application of an aerogel for separating notoginseng total saponins. Background Art

[0002] Panax notoginseng (Burk.) FH Chen is a traditional Chinese medicinal herb with extremely high medicinal value. Its main component is notoginseng total saponins. The composition of notoginseng's effective ingredients is complex, making the separation and purification of notoginseng total saponins challenging. Adsorption is a widely used separation and purification method. Currently, styrene resin is mainly used to adsorb notoginseng total saponins, using petrochemicals as raw materials. There is little research on green and environmentally friendly biomass adsorbents. It is of great significance to synthesize green and environmentally friendly adsorption materials for the separation and purification of notoginseng.

[0003] Montmorillonite is a clay mineral widely distributed in nature. It has a layered nanostructure and has the advantages of low price, stable performance, large specific surface area, and good adsorption capacity. The specific surface area, interlayer spacing and pore size of the modified montmorillonite are increased by acid-organic modification, thereby enhancing the adsorption performance; Nanocellulose is one of the most abundant natural polymers in nature, with high mechanical properties, rich hydroxyl groups, good biocompatibility, green environmental protection and renewable characteristics. Cellulose aerogel, as a porous material, has a high specific surface area and rich pore structure and is widely used in the field of adsorption. As a natural polymer aerogel, it can not only be used as a carrier, but also as a template combined with other materials to prepare composite aerogels with specific functions; Combining the characteristics of the two materials, a green and environmentally friendly composite aerogel is prepared and used for the separation and purification of Panax notoginseng total saponins. Summary of the invention

[0004] At present, macroporous resin is mainly used to separate and purify Panax notoginseng total saponins. The commonly used resin is styrene resin, which uses petrochemicals as raw materials. It is a non-renewable resource and will cause environmental pollution. Currently, there is little research on the adsorption of Panax notoginseng total saponins by biomass adsorbents. Therefore, biomass materials are used to synthesize green and environmentally friendly adsorbents for the separation and purification of Panax notoginseng total saponins.

[0005] The specific technical scheme of the present invention is: a method for preparing aerogel for separating notoginseng total saponins, characterized in that montmorillonite is firstly acid-organically modified, and then the modified montmorillonite-nanocellulose composite aerogel is prepared by freeze-drying.

[0006] Follow the steps below to implement it:

[0007] Add polyvinyl alcohol to the nanocellulose suspension and heat to dissolve, add the modified montmorillonite and stir evenly, pre-freeze and freeze-dry to obtain a montmorillonite and cellulose composite aerogel. The modification method of montmorillonite is as follows: take 20g MK and add it to a 1L conical flask, add 600mL of a 2% dilute hydrochloric acid solution by volume, seal it and place it in an oil bath, stir it mechanically at 50℃ for 5h, and the speed is 300r / min; after hydrochloric acid activation, let it stand to room temperature, centrifuge it at 4000r / min, discard the supernatant, repeat the above process with deionized water and wash it until the pH is 6, place the activated product in a vacuum drying oven, place it at 60℃ for 24h, grind and sieve it to obtain MA.

[0008] Take 10g of MA and 10g of CTAB and add them into a 1L conical flask, add 700mL of deionized water, seal it and place it in an oil bath, stir it mechanically at 65℃ for 24h; centrifuge it at 4000r / min, discard the supernatant, wash it with ethanol and deionized water respectively, and centrifuge it. Repeat the operation three times, place the modified montmorillonite in a vacuum drying oven, place it at 60℃ for 24h, grind and sieve it to obtain OMA.

[0009] Another object of the present invention is to apply the composite aerogel prepared by the above method to the separation and purification of notoginseng total saponins.

[0010] The beneficial effects of the present invention are:

[0011] 1. Modified montmorillonite-nanocellulose composite aerogels were prepared by freeze-drying technology for adsorption of Panax notoginseng total saponins. There are few studies on adsorption of Panax notoginseng total saponins by green and environmentally friendly biomass adsorbents. Most commonly used macroporous adsorption resins are based on aromatic compounds as the skeleton. Residual monomers in the preparation process are easy to pollute the adsorption process. The preparation method of CMPA is simple, green and environmentally friendly, with a wide source of raw materials and will not cause pollution to the adsorption process. It provides new ideas for the development of new adsorbents to separate and purify Panax notoginseng total saponins.

[0012] 2. The aerogel prepared by the present invention has the best adsorption effect on Panax notoginseng total saponins under the conditions of OMA ratio of 5%, dosage of 0.6 g, pH of 7, adsorption time of 3 h, adsorption temperature of 35°C, and initial concentration of 4 mg / mL. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 Flow chart for the preparation of CMPA

[0014] Figure 2 is the standard curve of Panax notoginseng total saponins

[0015] Figure 3 Scanning electron microscope images of MK, OMA, and CMPA

[0016] Figure 4Infrared spectra of MK, MA, OMA and CMPA

[0017] Figure 5 Zeta potential of MK, MA, OMA and CMPA under different pH conditions

[0018] Figure 6 Thermal stability curves of CMPA with different OMA ratios

[0019] Figure 7 N2 adsorption-desorption curves of OMA and CMPA

[0020] Figure 8 Porosity analysis diagram of CMPA with different OMA ratios

[0021] Fig. 9 Mechanical properties analysis diagram of CMPA with different OMA ratios

[0022] Fig.10 Optimization analysis of single factor effect on adsorption of Panax notoginseng total saponins

[0023] Fig.11 The adsorption performance analysis of OMA, montmorillonite aerogel without addition and CMPA on PNS DETAILED DESCRIPTION

[0024] Examples 1-5

[0025] According to the combination of the examples in Table 1, the preparation of CMPA was carried out according to the following steps.

[0026] Step 1: Acid modification of montmorillonite

[0027] Take 20g MK and add it to a 1L conical flask, add 600mL of 2% dilute hydrochloric acid solution, seal it and place it in an oil bath, stir it mechanically at 50℃ for 5h, and the speed is 300r / min; after hydrochloric acid activation, let it stand to room temperature, centrifuge it at 4000r / min, discard the supernatant, repeat the above process with deionized water to wash it to pH 6, place the activated product in a vacuum drying oven, place it at 60℃ for 24h, grind and sieve it to obtain MA.

[0028] Step 2: Organic modification of montmorillonite

[0029] Take 10g MA and 10g CTAB and add them into a 1L conical flask, add 700mL deionized water, seal and place in an oil bath, mechanically stir at 65℃ for 24h, centrifuge at 4000r / min, discard the supernatant, wash with ethanol and deionized water respectively, centrifuge, repeat the operation three times, place the modified montmorillonite in a vacuum drying oven, place at 60℃ for 24h, grind and sieve to obtain OMA.

[0030] Step 3: Preparation of CMPA

[0031] Polyvinyl alcohol was added into the nanocellulose suspension, heated at 110°C and 200 r / min to dissolve, OMA was added and stirred evenly, and the suspension was pre-frozen and freeze-dried to obtain a composite aerogel of montmorillonite and cellulose.

[0032] Table 1 Combination ratio of ingredients for CMPA preparation

[0033] Example CNF(g) OMA(g) PVA(g) Example 1 97 1 2 Example 2 95 3 2 Example 3 93 5 2 Example 4 91 7 2 Example 5 89 9 2 In order to prove the adsorption effect of the present invention, the inventor conducted a scientific experiment. The specific experimental process and data are as follows:

[0035] Experiment 1

[0036] Drawing of standard curve of Panax notoginseng total saponins:

[0037] Use 70% methanol solution to prepare 10 mL of Panax notoginseng total saponins standard solution, in which the content of Panax notoginseng saponin R1 is 10.1 mg, and the contents of ginsenosides Rg1, Re, Rb1 and Rd are 20.4, 10.3, 20.4 and 10 mg, respectively. The standard curve was measured by changing the injection volume, and the injection volume gradient was set to: 1, 3, 5, 7, 9, 12, 15 μL. For the same concentration of standard solution, different injection volumes are proportional to the peak area, and the peak area (Y) is proportional to the mass concentration (X); refer to the liquid chromatography conditions in the 2020 version of the "Chinese Pharmacopoeia": Shimadzu ShimNex UP C18 chromatographic column, (5 μm, 4.6×250 mm). With water as mobile phase A and acetonitrile as mobile phase B, gradient elution method: 0-25min, 20% B; 25-50min, 20%-46% B; 50-60min, 46%-55% B; 60-65min, 55% B; 65-75min, 20% B; column temperature 30°C, flow rate 1.5mL / min, detection wavelength 203nm; thus, the linear relationship can be constructed as follows: Panax notoginseng saponin R1: Y=923.1054X-1.9703, R 2 =0.9999; ginsenoside Rg1, Re, Rb1 and Rd are: Y = 1688.2599X-6.5205, R 2 =0.9999; Y=882.2536X-5.9552, R 2 =0.9998; Y=1169.2806X+2.3101, R 2 =0.9999; Y=867.4212X-2.4502, R 2 =0.9999.

[0038] Experiment 2

[0039] Effect of different OMA ratios on adsorption performance:

[0040] Take 20 mL of 2 mg / mL Panax notoginseng total saponin solution in a 50 mL conical flask, weigh 0.4 g of CMPA with OMA content of 1%-9% in each conical flask, place it in an oscillating shaker, 25°C, 150 r / min, oscillate for 24 hours, centrifuge at 10000 r / min for 5 minutes after adsorption, take 1 mL of supernatant, measure the peak area at 203 nm using semi-preparative HPLC Agilent 1260, and calculate the concentration of the adsorbed solution using the standard curve.

[0041] Experiment 3

[0042] Effect of different dosage on adsorption performance:

[0043] Take 20 mL of 2 mg / mL Panax notoginseng total saponin solution in a 50 mL conical flask, weigh 0.2-0.8 g CMPA in each conical flask, place it in an oscillating shaker, 25°C, 150 r / min, oscillate for 24 h, centrifuge at 10000 r / min for 5 min after adsorption, take 1 mL of supernatant, measure the peak area at 203 nm using a semi-preparative HPLC Agilent 1260, and calculate the concentration of the adsorbed solution using the standard curve.

[0044] Experiment 4

[0045] Effect of different pH on adsorption performance:

[0046] The pH was adjusted to 3-11 with 0.1M NaOH and 0.1M HCl, and a 2 mg / mL Panax notoginseng total saponin solution with a pH of 3-11 was prepared. 20 mL of Panax notoginseng total saponin solution with different pH values ​​was taken in conical flasks respectively, 0.4 g CMPA was weighed in a conical flask, and placed in an oscillating shaker at 25°C, 150 r / min, and oscillated for 24 h. After the adsorption was completed, centrifuged at 10000 r / min for 5 min, 1 mL of supernatant was taken, and the peak area was measured at 203 nm using a semi-preparative HPLC Agilent 1260, and the concentration of the adsorbed solution was calculated using the standard curve.

[0047] Experiment 5

[0048] Effect of different adsorption time on adsorption performance:

[0049] Take 200 mL of 2 mg / mL Panax notoginseng total saponin solution in a 250 mL conical flask, weigh 4 g CMPA in the conical flask, place it in an oscillating shaker, 25°C, 150 r / min, take 2 mL every 10 min from 0 to 60 min, sample every 30 min from 60 to 180 min, sample every 60 min from 180 to 300 min, centrifuge at 10000 r / min for 5 min, take 1 mL of supernatant, measure the peak area at 203 nm using a semi-preparative HPLC Agilent 1260, and calculate the concentration of the adsorbed solution using the standard curve.

[0050] Experiment 6

[0051] Effect of different initial concentrations on adsorption performance:

[0052] Prepare 2-8 mg / mL Panax notoginseng total saponin solutions respectively, take 20 mL of each into a 50 mL conical flask, weigh 0.4 g CMPA into the conical flask, place it in an oscillating shaker, 25 ° C, 150 r / min, oscillate for 3 hours, centrifuge at 10000 r / min for 5 minutes after adsorption, take 1 mL of supernatant, measure the peak area at 203 nm using a semi-preparative HPLC Agilent 1260, and calculate the concentration of the adsorbed solution using the standard curve.

[0053] Experiment 7

[0054] Effect of different temperatures on adsorption performance:

[0055] Take 20 mL of 4 mg / mL Panax notoginseng total saponin solution in a 50 mL conical flask, weigh 0.6 g CMPA in the conical flask, place it in an oscillating shaker, set the temperature to 15-45 ° C, 150 r / min, oscillate for 3 hours, centrifuge at 10000 r / min for 5 minutes after adsorption, take 1 mL of supernatant, measure the peak area at 203 nm using semi-preparative HPLC Agilent 1260, and calculate the concentration of the adsorbed solution using the standard curve.

[0056] Experiment 8

[0057] The composite aerogel was characterized by a series of tests including SEM, FTIR, Zeta potential, thermogravimetric analysis, BET, porosity, and mechanical properties. Result analysis:

[0058] Experiment 1: Standard curve of total saponins of Panax notoginseng Figure 2 Shown

[0059] SEM images of modified montmorillonite and composite aerogel Figure 3 As shown, the surface of the modified montmorillonite has more wrinkles and is rougher, which is conducive to adsorption; the presence of nanocellulose and montmorillonite can be observed in the composite aerogel at the same time, proving that the material preparation is successful.

[0060] like Figure 4 As shown, at 2846 and 2920 cm -1 The antisymmetric stretching peak and symmetric stretching peak of CH2 are at 1472cm -1 The angular vibration appeared and CTAB had long-chain alkyl groups, indicating that the montmorillonite was successfully modified.

[0061] like Figure 5 As shown, MK carries a negative charge, which decreases after acidic modification. The organic surfactant carries a positive charge after intercalation into montmorillonite, and CMPA carries a positive charge under different pH conditions.

[0062] To investigate the thermal stability of modified montmorillonite and aerogel, Figure 6 As shown in the figure, the degradation of aerogel is divided into four stages. In the first stage, the mass of aerogel is slightly lost in the range of 40-128°C, and the residual water in the aerogel evaporates; in the second stage, the mass decreases significantly in the range of 175-280°C, which is due to the initial degradation of PVA and CNF; in the third stage, the mass of the sample is significantly lost in the range of 290-395°C, which is due to the thermal decomposition of the main structural substances CNF and PVA; in the fourth stage, the mass decreases slightly in the range of 400-530°C, and a very small amount of montmorillonite undergoes thermal decomposition, with a mass loss of about 1%.

[0063] like Figure 7 As shown, it is a type IV isotherm containing an H4 type hysteresis loop, indicating the existence of micropores and mesopores with an average pore size of 13.43 nm.

[0064] like Figure 8 As shown, the porosity of CMPA is above 80%.

[0065] like Fig. 9 As shown, the maximum compressive strength of CMPA increases with the increase of OMA proportion, and the maximum compressive strength is 863KPa.

[0066] Experiment 2-6 Fig.10 As shown, the adsorption effect of Panax notoginseng total saponins was best when the OMA ratio was 5%, the dosage was 0.6 g, the pH was 7, the adsorption time was 3 h, the adsorption temperature was 35 ° C, and the initial concentration was 4 mg / mL.

[0067] like Fig.11 As shown, it indicates that modified montmorillonite and nanocellulose aerogel have a certain adsorption effect on Panax notoginseng total saponins, and the composite aerogel prepared by combining the two materials has a better adsorption effect on Panax notoginseng total saponins, with an adsorption amount of 49.6 mg / g and an adsorption rate of 95.1%.

[0068] The above embodiments describe the present invention in detail. These embodiments are only used to illustrate the present invention and do not limit the protection scope of the present invention.

Claims

1. A method for preparing aerogel for separating notoginseng total saponins, characterized in that: The preparation method includes the following: Polyvinyl alcohol is added into the nanocellulose suspension and heated to dissolve, and then pre-frozen and freeze-dried to obtain cellulose aerogel.

2. A method for preparing aerogel for separating notoginseng total saponins as claimed in claim 1, the preparation method comprising the following steps: Polyvinyl alcohol is added into the nanocellulose suspension and heated to dissolve, and the modified montmorillonite is added and stirred evenly, and the mixture is pre-frozen and freeze-dried to obtain a composite aerogel of montmorillonite and cellulose.

3. A method for preparing aerogel for separating notoginseng total saponins as claimed in claim 1 or 2, characterized in that: The mass of the polyvinyl alcohol is 2% of the total mass.

4. A method for preparing aerogel for separating notoginseng total saponins as claimed in claim 1 or 2, characterized in that: Prefreeze at 4℃ for 4h and freeze-dry for 48h.

5. A method for preparing aerogel for separating notoginseng total saponins as claimed in claim 1 or 2, characterized in that: Dissolve the polyvinyl alcohol at 110°C with mechanical stirring for 1 h.

6. The method for preparing aerogel for separating notoginseng total saponins as claimed in claim 2, characterized in that: The mass of modified montmorillonite is 1%, 3%, 5%, 7% and 9% of the total mass.

7. An aerogel for separating Panax notoginseng total saponins, prepared by the method according to any one of claims 1 to 6.

8. Use of the composite aerogel as claimed in claim 7 for separation and purification of notoginseng total saponins in Panax notoginseng.